2010
DOI: 10.1172/jci39812
|View full text |Cite
|
Sign up to set email alerts
|

Replacing adenoviral vector HVR1 with a malaria B cell epitope improves immunogenicity and circumvents preexisting immunity to adenovirus in mice

Abstract: Although adenovirus (Ad) has been regarded as an excellent vaccine vector, there are 2 major drawbacks to using this platform: (a) Ad-based vaccines induce a relatively weak humoral response against encoded transgenes, and (b) preexisting immunity to Ad is highly prevalent among the general population. To overcome these obstacles, we constructed an Ad-based malaria vaccine by inserting a B cell epitope derived from a Plasmodium yoelii circumsporozoite (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
80
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(84 citation statements)
references
References 30 publications
3
80
1
Order By: Relevance
“…Our data contrast with two previous studies that reported substantial evasion of Ad5 immunity by Ad5 vectors in which single HVRs (HVR1, HVR5) were mutated (1,15). In our studies, swapping just HVR1 (Fig.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Our data contrast with two previous studies that reported substantial evasion of Ad5 immunity by Ad5 vectors in which single HVRs (HVR1, HVR5) were mutated (1,15). In our studies, swapping just HVR1 (Fig.…”
contrasting
confidence: 99%
“…However, the relative importances of the seven individual HVRs as NAb epitopes remain incompletely understood, and recent studies have suggested that Ad5 NAb responses may actually be focused primarily on one specific HVR, such as HVR1 or HVR5 (1,15). In this study, we characterized the contribution of individual hexon HVRs as Ad5 NAb epitopes.…”
mentioning
confidence: 97%
“…Incorporation of identical or distinct epitopes in multiple hexon HVRs or multiple capsid proteins is possible and may enhance the magnitude or breadth of an antibody response to capsid display recombinants. We and others have demonstrated induction of robust T-cell responses against antigens delivered by live adenovirus recombinants that express whole proteins as transgenes (17,18,36). Recombinants that both contain a transgene and display a relevant epitope on the capsid therefore might effectively induce both humoral and cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoviruses that display exogenous epitopes on the surfaces of their capsids (capsid display recombinants) are potently immunogenic in mice (10)(11)(12)17). Capsid display recombinants that expressed either the central repeat B-cell epitope (NANP) 5 or a combined B-and T-cell epitope NANPNVDP(NANP) 4 induced high-titer P. falciparum CSP antibodies, and serum from (NANP) 5 -immunized mice (the only ones examined) neutralized sporozoites in an in vitro assay (11).…”
mentioning
confidence: 99%
“…Substitution of Ad5 HVRs 7, 8, and 9 with Ad43 HVRs had minimal impact on the immune avoidance phenotype and did not reduce vector yields in complementing cells. Earlier published studies showed that Ad5 vectors with modifications to only HVR1 (63) or HVR5 (64) avoided Ad5 NAb in vitro and could induce transgene-specific immune responses in animals previously exposed to Ad5. However, more recent work indicates that Ad5-, Ad3-, and Ad7-specific NAb target multiple HVRs (65,66).…”
Section: Discussionmentioning
confidence: 99%